An evaluation of isotopic (δ2H) methods to provide estimates of avian breeding and natal dispersal. Issue 4 (2nd April 2019) - López‐Calderón, C.; Van Wilgenburg, Steven L.; Roth, Amber M.; Flaspohler, David J.; Hobson, Keith A.
Abstract: Natal and breeding dispersal represents an important component of animal demography and metapopulation theory. This phenomenon also has implications for conservation and management because understanding movements of individuals potentially allows the identification of key habitats that may be acting as population sources or sinks. Intrinsic markers such as stable isotope abundance in tissues that can be associated with provenance can provide a coarse but pragmatic solution to understanding such movements. Different methodologies have been proposed to quantify natal and breeding dispersal by using stable isotope analyses of keratinous tissues (hair, feathers), each of them with their own advantages and limitations. Here, we compared results provided by four different methods to estimate dispersal (three already published and one novel) in animals using stable isotope measurements. We used a single large dataset of feather δ 2 H values from golden‐winged warblers ( Vermivora chrysoptera ) representing five different populations breeding in North America to compare model results. We propose one method as the most adequately supported by data, and we used this method to demonstrate how biological factors explaining dispersal status can be identified and geographical origins of immigrants inferred. Our results point to a generalized methodological approach to using stable isotope data to study immigration and dispersal in birds and other animals.